2016
DOI: 10.1155/2016/4982676
|View full text |Cite
|
Sign up to set email alerts
|

Growing-Related Changes in Arterial Properties of Healthy Children, Adolescents, and Young Adults Nonexposed to Cardiovascular Risk Factors: Analysis of Gender-Related Differences

Abstract: The aims of our work were to determine normal aging rates for structural and functional arterial parameters in healthy children, adolescents, and young adults and to identify gender-related differences in these aging rates. Methods. 161 subjects (mean: 15 years (range: 4–28 years), 69 females) were studied. Subjects included had no congenital or chronic diseases, nor had they been previously exposed to traditional cardiovascular risk factors. Arterial parameters assessed were (1) central blood pressure (BP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
2
28
0
1
Order By: Relevance
“…Three examinations were taken from both common carotid arteries and means were calculated to estimate the overall IMT. cIMT was assessed by sex-specific curves for age and increased cIMT was defined as cIMT>90%, which shows atherosclerosis 14 .…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 99%
“…Three examinations were taken from both common carotid arteries and means were calculated to estimate the overall IMT. cIMT was assessed by sex-specific curves for age and increased cIMT was defined as cIMT>90%, which shows atherosclerosis 14 .…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 99%
“…Healthy subjects (n = 1449; 3-88 years) from the community were considered for enrolment (Table 1) [18][19][20][21][22]. Hypertension, diabetes or dyslipidemia were considered present if the subject reported being in treatment and/or a previous diagnosis of their condition.…”
Section: Methodsmentioning
confidence: 99%
“…[RIs]) of cardiovascular variables in several populations; with special emphasis which considers childhood, adolescence and/or adult life as a continuum [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Aging is an inevitable and integral factor of childhood; therefore, the results obtained from these studies should be interpreted carefully . Few longitudinal studies have reported on the risk factors of atherosclerotic change in children .…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15] Aging is an inevitable and integral factor of childhood; therefore, the results obtained from these studies should be interpreted carefully. 16 Few longitudinal studies have reported on the risk factors of atherosclerotic change in children. [17][18][19] The aim of the present study was hence to conduct a longitudinal study on the effect of lifestyle on PWV in junior high school students over a period of 3 years, from seventh to ninth grades.…”
mentioning
confidence: 99%